Pengaruh Kepemimpinan Kepala Sekolah dan Kebijakan Sekolah terhadap Mutu Pendidikan - Putra Hafizh Kanz (BISMA : Business and Management Journal, 2025)
This study seeks to examine the impact of principal leadership and school policies on educational quality at SDIT Az-Zahra. This study aims to ascertain the impact of principal leadership and school policies on educational quality. The employed methodology is a quantitative approach utilizing survey methodologies and multiple regression analysis. The study's population comprised 21 educators at SDIT Az-Zahra. The statistical study results demonstrate that principal leadership  significantly affects educational quality, evidenced by a coefficient of determination of 0.537 for this relationship. This indicates that 53.7% of educational quality is determined by principal leadership, whereas 46.3% is attributable to other variables. Secondly, school policy exerts an influence on educational quality, with a coefficient of determination of 0.454, indicating that 45.4% of educational quality is attributable to school policy, while 54.6% is influenced by other factors. Third, there exists a substantial correlation of 0.674 between principal leadership and school policy for educational quality, indicating that 67.4% of educational quality is determined by these factors, while 32.6% is attributable to other influences. As a practical implication, this study recommends that the foundation and school management work synergistically to continuously enhance adaptive leadership competencies and formulate strategic school policies to optimize sustainable educational quality.